A case study of literacy instruction delivered to kindergarten struggling readers within the response to intervention model in three classroom settings - Zelenka, Valerie Lynn (Kansas State University, 2010)
A portion of the 2004 reauthorization of the Individuals with Disabilities Education Act (IDEA, 2004), Response to Intervention (RtI), aims to prevent unnecessary student placement in special education. The intent of RtI is to provide all students with effective classroom instruction first and afford low-performing students with increasingly intensive, individualized interventions (Fuchs, Fuchs, & Vaughn,2008). Although there is considerable information available in regard to the effectiveness of the multi-tiered model of the Response to Intervention approach to deliver intervention services to struggling readers (Speece & Walker, 2007), very little is known about implementing RtI in the schools (Allington, 2009). This qualitative, exploratory, collective case study was conducted during the fall/spring semesters of the 2009/2010 school year between November 16, 2009 and February 26, 2010. This study investigated how three kindergarten classroom teachers, located in two elementary schools, delivered Tier 2 literacy instruction to kindergarten struggling readers within the Response to Intervention model in the classroom setting. Multiple data sources were gathered from interviews with administrators and teachers, guided conversations with students, classroom observations and field notes, and documents/artifacts. Data were collected and analyzed during three phases of the study. This study’s findings established that in the new era of Response to Intervention (RtI), teachers were able to apply literacy instructional approaches and pedagogy based on their teaching philosophy to address the needs of at-risk struggling readers within the kindergarten classroom environment. However, data analysis revealed dissimilar perceptions of the three case study teachers regarding their roles and responsibilities teaching literacy within the Response to Intervention approach which influenced how they delivered Tier 2 intervention instruction. The three classroom teachers utilized the modeled, shared, and guided approaches to literacy instruction and provided lessons in phonemic awareness and phonics during Tier 2 small group literacy interventions. In addition, the data collection and analysis identified three pedagogies which occurred during Tier 2 instruction: 1) monitoring of learning; 2) encouraging and supportive learning environments; and 3) feedback and reinforcement. Data analysis also revealed the student participant benefits included positive attitudes towards reading, students’ perception of themselves as self-confident and motivated readers, development of an emerging love of reading, and enjoyment of practicing their reading skills in small groups.
Keywords: Literacy; Struggling readers; Response to Intervention; Tier 2 intervention; Education, Reading (0535)